1989
DOI: 10.1016/0735-1097(89)90104-6
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography in infective endocarditis: Reassessment of prognostic implications of vegetation size determined by the transthoracic and the transesophageal approach

Abstract: In 105 patients with active infective endocarditis, disease-associated complications defined as severe heart failure (New York Heart Association class IV), embolic events and in-hospital death were correlated to the vegetation size determined by both transthoracic and transesophageal echocardiography. A detailed comparison between anatomic and echocardiographic findings, performed in a subgroup of 80 patients undergoing surgery or necropsy, revealed that true valvular vegetations can be reliably identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
241
3
36

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(286 citation statements)
references
References 28 publications
6
241
3
36
Order By: Relevance
“…[1][2][3][4] Complication rate in TEE is low, 5 but the procedure is semi-invasive, time consuming, and often not readily available everywhere. Therefore, it might be applied primarily to patients with stroke of undetermined etiology (ie, patients showing normal results in ECG, carotid ultrasound, and TTE, who are candidates for oral anticoagulation [OA]).…”
mentioning
confidence: 99%
“…[1][2][3][4] Complication rate in TEE is low, 5 but the procedure is semi-invasive, time consuming, and often not readily available everywhere. Therefore, it might be applied primarily to patients with stroke of undetermined etiology (ie, patients showing normal results in ECG, carotid ultrasound, and TTE, who are candidates for oral anticoagulation [OA]).…”
mentioning
confidence: 99%
“…The highest incidence of embolic complication is observed in infective endocarditis due to hemolytic streptococcus C species as well as Staphyrococcus aureus, resulting in a high mortality rate (17)(18)(19)(20). It has been reported that size and mobility of the vegetation are highly sensitive in identifying patients at risk for embolic events (15). In the present patient, the size of the mobile vegetation became progressively enlarged over a few days despite maximal antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 64%
“…Surgical therapy is recommended for patients with infective endocarditis who have congestive heart failure, perivalvular invasive disease, uncontrolled infection despite maximal antimicrobial therapy, or episodes of embolization with residual large vegetation (9,15,16). The highest incidence of embolic complication is observed in infective endocarditis due to hemolytic streptococcus C species as well as Staphyrococcus aureus, resulting in a high mortality rate (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation length of greater than 15 mm was an independent predictor of 1-year mortality. It is unclear whether IE affecting a particular valve leads to a higher probability of embolization; mitral valve involvement has been suggested as conferring a higher embolic risk, especially with vegetations over 10 mm [12][13][14]16], while others have concluded that embolic risk is independent of vegetation location [10,11].…”
Section: The Long and Short Of Vegetations In Infective Endocarditismentioning
confidence: 99%
“…• Timing of echocardiography with respect to onset of patient symptoms and infrequent follow-up echocardiograms to assess vegetation status; [10][11][12][13][14], while others have not [15]. The latter study was performed before the era of TEE and vegetations were visualized by TTE in only 38% of patients [15].…”
Section: The Long and Short Of Vegetations In Infective Endocarditismentioning
confidence: 99%